Metastable precursor structures in hydrogen-infused super duplex stainless steel microstructure – An operando diffraction experiment. (November 2020) - Örnek, Cem; Larsson, Alfred; Harlow, Gary S; Zhang, Fan; Kroll, Robin; Carlà, Franceso; Hussain, Hadeel; Kivisäkk, Ulf; Engelberg, Dirk L; Lundgren, Edvin; Pan, Jinshan
Graphical abstract: Highlights: Hydrogen infusion causes tensile lattice deformation at the near-surface. The austenite underwent more lattice deformation than the ferrite. Hydrogen-induced lattice strain formation is reversible. Metastable quasi hydrides are formed in the austenite. The degradation of the austenite matters predominantly in hydrogen embrittlement. Abstract: We report the evolution of metastable precursor structures during hydrogen infusion in the near-surface region of a super duplex stainless steel. Grazing-incidence x-ray diffraction was employed to monitor, operando, the lattice degradation of the austenite and ferrite phases. Electrochemical hydrogen charging resulted in the splitting of the diffraction peaks of the austenite phase, suggesting the evolution of a metastable precursor structure. This may be explained by the formation of quasi-hydrides, which convert back into the austenite parent structure during hydrogen effusion. The ferrite showed less lattice deformation than the austenite and no phase transformation.